The Effect of Forest Management on Stand Structure and Tree Diversity in the Sal (Shorea robusta) Forest of Nepal - Ranabhat, S.; Fehrman, L.; Malla, R. (Indian Forester, 2016)
This study aimed to assess the stand structure and tree diversity of the Sal (Shorea robusta) forest under different management regimes, i.e. National Park (NP) and Buffer Zone Community Forest (BZCF). Three parallel transects, 200 m apart, were laid out in two different management types. Concentric circular plots were laid out systematically with a distance of 150 m along each transect. Altogether 30 and 26 sample plots were employed in the NP and BZCF respectively. Number of trees, poles and regenerations per hectare was found to be higher in the NP whilst the number of saplings was found higher in the BZCF. Estimators of species diversity (Jack 2, Chao 2) and Species diversity index (Shannon Wiener Index) identified the NP as more diverse in tree and pole whilst the BZCF was more diverse in sapling and seedling. The overall results show that community based forest management in buffer zone areas is one of the best forest management options to restore the degraded Sal forest.